Historic win for UMP civil engineering undergraduates at Taiwan IEYI 2012 - UMP, PNC
Universiti Malaysia Pahang (UMP) recorded another historic and momentous win when four undergraduates from the Faculty of Civil Engineering & Earth Resources (FKASA) coveted two gold and two silver medals, as well as six additional special awards at the International Exhibition for Young Inventors (IEYI 2012) in Taiwan recently.